Evaluation of the risk of metachronous multiple squamous cell carcinoma of the head and neck after transoral surgery based on the genetic polymorphisms of alcohol dehydrogenase 1B and aldehyde dehydrogenase 2. (21st September 2021) - Inoue, Masaki; Shimizu, Yuichi; Taniguchi, Masanobu; Kimura, Yuki; Furuhashi, Hiroto; Dobashi, Akira; Ikeya, Takashi; Goda, Kenichi; Kato, Masayuki; Kato, Mototsugu; Sakamoto, Naoya; Watanabe, Akihito
Abstract: Patients with superficial head and neck squamous cell carcinoma (HNSCC) can be completely treated by techniques of transoral surgery (TOS). The aim of this study was to evaluate the risk of metachronous multiple HNSCC arising after TOS based on alcohol dehydrogenase 1B (ADH1B) and aldehyde dehydrogenase 2 (ALDH2). We registered patients who underwent TOS for superficial HNSCC. Buccal cell samples were obtained by using a cotton swab to examine two single nucleotide polymorphisms in ADH1B and ALDH2 genotyping. We used Cox proportional hazards models to examine the risk of metachronous HNSCC. A total of 198 patients who underwent TOS for HNSCC were evaluated. In multivariate analysis, risks for second HNSCC were ADH1B*1/*1 [hazard ratio (HR), 1.88; 95% confidence interval (CI), 1.11–3.19; P = 0.02], ALDH2*1/*2 (HR, 2.11; 95% CI, 1.00–5.16; P = 0.048) and alcohol consumption before TOS (HR, 1.17; 95% CI, 1.06–1.27; P = 0.01). The 5-year incidence rates of second primary HNSCC in the temperance group and the non-temperance group were 20.8 and 46.5%, respectively (HR, 0.54; 95% CI, 0.31–0.92; P = 0.02). Cumulative development rates of third HNSCC in the temperance group and non-temperance group at 10 years were 11.3 and 36.1%, respectively (HR, 0.19; 95% CI, 0.03–0.65; P = 0.006). ADH1B*1/*1, ALDH2*1/*2 and moderate or heavy alcohol consumption before treatment are independent risk factors of metachronous HNSCC. Since it was shown that temperance decreased the incidences of second and third metachronous HNSCC, advice to discontinue alcohol drinking is necessary. Abstract : Our study showed that ADH1B*1/*1, ALDH2*1/*2 and alcohol consumption before treatment were independent risk factors for metachronous head and neck squamous cell carcinoma (HNSCC). In addition, continuing to drink alcohol increased the incidence of metachronous HNSCC.